1967
DOI: 10.1192/bjp.113.500.761
|View full text |Cite
|
Sign up to set email alerts
|

Parental Bereavement in Childhood: M.M.P.I. Profiles in a Depressed Population

Abstract: Recent studies of childhood bereavement in depressive populations (Forrest, Fraser, and Priest, 1965; Munro, 1966) indicate that parental bereavement in childhood may be of aetiological significance in depressive illness (Forrest et al., 1965) and may affect the severity of the clinical picture (Munro, 1966).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Gay & Tonge (1967), indeed, found the risk of parental' loss' (including separations) was greater in reactive than endogenous depressives. In contrast, Wilson et al (1967) found that bereaved depressive subjects had generally psychotic profiles on the MMPI, and that nonbereaved depressives had neurotic profiles. Forrest et al (1965) found that parental death did not distinguish between endogenous and neurotic depressives.…”
Section: Inconsistent Findingsmentioning
confidence: 71%
See 1 more Smart Citation
“…Gay & Tonge (1967), indeed, found the risk of parental' loss' (including separations) was greater in reactive than endogenous depressives. In contrast, Wilson et al (1967) found that bereaved depressive subjects had generally psychotic profiles on the MMPI, and that nonbereaved depressives had neurotic profiles. Forrest et al (1965) found that parental death did not distinguish between endogenous and neurotic depressives.…”
Section: Inconsistent Findingsmentioning
confidence: 71%
“…Archibald et al (1962) found 'bereaved' and 'non-bereaved' psychiatric patients to be remarkably similar in their personality profiles. Wilson et al (1967) found the scores of bereaved depressed patients on the four psychotic subscales to be higher than non-bereaved depressed patients. However, this difference was only statistically significant for the schizophrenia scale-a rather unusual finding.…”
Section: Personalitymentioning
confidence: 80%
“…The effect of early loss has been thought so critical to development that much research has been devoted to studying psychological outcomes of bereaved children (Berlinsky & Biller, 1982; Finkelstein, 1988; Tennant, Bebbington, & Hurry, 1981). Developmental theories, retrospective analyses of depressed adults, and an intuitive sense of trauma following early loss have led researchers to try repeatedly to link this experience with adult depression (Barnes & Prosen, 1985; Finkelstein, 1988; Klerman & Weissman, 1986) and other adult psychopathology (Brown, 1966; Dietrich, 1984; Wilson, Alltop, & Buffaloe, 1967). To date, most of this research has been limited in that it has failed to account for confounding variables associated with loss, including age at time of loss, gender of deceased parent, cause of death, time elapsed between loss and assessment, and quality of relationship with deceased and surviving parents (Berlinsky & Biller, 1982; Tennant et al, 1981).…”
mentioning
confidence: 99%